Dynamics Analysis of Helical Gear with Time-varying Stiffness and Tooth Pitch Error - Zhang Liu; Wu Xuncheng; Xu Junjian; Zhang Juecheng; Zhang Yanjie (Jixie chuandong)
The automobile transmission gear is the power carrier of a transmission system,the vibration characteristic of the transmission is largely determined by the dynamics characteristic. The time-varying contact line method is used to study the theoretical time-varying meshing stiffness theory solution. Combining with the internal incentives,such as the tooth pitch error,the shaft coupling nonlinear dynamics model of helical gear pair bending and twisting is established. The Runge-kutta method is used for numerical solution,the time-domain response curves and the frequency spectrum diagrams of the vibration response of a helical gear pair are obtained. The results show that,the smaller the time-varying mesh stiffness,the degree of gear vibration increases more rapidly. After joining the tooth pitch error,the vibration acceleration time-domain characteristics with axial vibration change is most obvious,and the smaller the tooth pitch error,the slower increase in the intensity of the vibration.